Implementing of Religiosity and Emotional Intelligence Towards Educational Sustainability on Teacher Performance - Supriyadi; Soelton, Mochamad (ARE Publisher, 2024)
Objectives: Teacher performance is an important component and influences improving the quality of education, so managing teacher performance is important to achieve the goals of quality education. This research aims to determine the influence of creativity, religiosity and emotional quetient on teacher performance in motivational moderation (study at the Dinamika Cikarang Education Development Foundation). Methodology: This research method uses quantitative methods, the population in this research is 110 teachers. The sampling technique in the research used the Slovin formula, with a total sample of 86 teachers. Research data was collected through distributing questionnaires, data analysis using Structural Equation Model – Partial Least Square (SEM-PLS) Finding: The results of the research show that: creativity, religiosity and emotional quetient have a positive and significant effect on teacher performance, motivation is not able to moderate the influence of emotional quetient on teacher performance, motivation is able to partially moderate teacher performance, and motivation is able to partially moderate the effect of religiosity on performance Teacher. Conclusion:The contribution of this research is the findings that can be used as a basis for human resource management policies in improving company performance.